A STUDY OF IMMUNOGENIC AND PROTECTIVE PROPERTIES OF THE HEAT-STABLE LETHAL TOXIN OF YERSINIA PSEUDOTUBERCULOSIS AND ITS EFFECTS UPON HEMATOLOGICAL AND BLOOD CYTOKINE PARAMETERS OF LABORATORY MICE - A. V. Tsybulsky; N. F. Timchenko; E. Ya. Kostetsky; N. S. Vorobieva (Медицинская иммунология, 2014)
The article presents some data concerning antigenic and immunogenic properties of the lethal heat-stable toxin (HST) from Yersinia pseudotuberculosis, a protein with molecular weight of 45 kDa. The mice,following double immunization with HST at a dose of 0.1 mg per mouse, displayed higher antibody production, in comparison with a dose of 0.01 mg/mouse. The appropriate differences were revealed with regard ofleukocyte responses, i.e., development of leukopenia, neutropenia, lymphopenia upon immunization with the 0.01 mg of HST per mouse, whereas leukocytosis, and increase in lymphocytes and monocytes was detected after a dose of 0.1 mg/mouse. We detected some doseependent differences in cytokine-modulating activity. I.e., at HST dose of 0.01 mg per mouse, we detected mostly proinflammatory, acutehase responses, whereas a dose of 0.1 mg/mice caused induction of . IFNγ and cytokines promoting lymphocyte proliferation and antibody production by day +17. Upon double immunization of mice, the toxin showed protective properties when injecting them with lethal dose of Y. pseudotuberculosis. A lagging activation of antibody producers duringHST response suggests a need for searching effective adjuvant tools of enhancement and acceleration of specific humoral immune reactions against this antigen.